2009
DOI: 10.1088/0004-637x/692/1/411
|View full text |Cite
|
Sign up to set email alerts
|

Direct Calculation of the Radiative Efficiency of an Accretion Disk Around a Black Hole

Abstract: Numerical simulation of magnetohydrodynamic (MHD) turbulence makes it possible to study accretion dynamics in detail. However, special effort is required to connect inflow dynamics (dependent largely on angular momentum transport) to radiation (dependent largely on thermodynamics and photon diffusion). To this end we extend the flux-conservative, general relativistic MHD code HARM from axisymmetry to full 3D. The use of an energy conserving algorithm allows the energy dissipated in the course of relativistic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
282
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(291 citation statements)
references
References 50 publications
3
282
0
6
Order By: Relevance
“…These equations amount to conservation of baryon number density and conservation of stress-energy (see Noble et al (2009) for more details). Taken together, they can be written as…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…These equations amount to conservation of baryon number density and conservation of stress-energy (see Noble et al (2009) for more details). Taken together, they can be written as…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…See Beckwith et al (2008), Shafee et al (2008), and Noble et al (2009) for recent discussions of this issue.…”
Section: Implications For Spectral Hardening and Continuum Spin Estimmentioning
confidence: 99%
“…Shafee et al (2008) recently simulated a thin disk around a Schwarzschild hole and suggested that the ISCO stress cuts off sharply when the disk is thin. On the other hand, Noble, Krolik, & Hawley (2009) find additional ISCO stress even for a relatively thin disk. They further considered the observational implications of the ISCO stress using simple emission and absorption models coupled with relativistic ray tracing.…”
mentioning
confidence: 84%